Rethinking the Applications of Ionic Liquids and Deep Eutectic Solvents in Innovative Nano-Sorbents - Nie, Lirong; Toufouki, Sara; Yao, Shun; Guo, Dong (Frontiers in Chemistry, 2021)
With the development of green chemistry and nano materials, new green solvents are one of important hotspots in the field of nano materials. Ionic liquids (ILs) and deep eutectic solvents (DESs) as green solvents are being applied in the innovation of nano-sorbents, including nanoparticles, nanogels and nanofluid. The applications of ILs and DESs in nano-sorbents are briefly commented. ILs and DESs are often used as carriers/modifiers/disperser of nano-sorbents to enhance the adsorption capacity and selectivity in extraction procedure. Various extraction technologies, such as solid-phase extraction, solid-phase microextraction, micro-solid phase extraction, hollow fiber liquid phase microextraction and magnetic solid-phase extraction, have also been promoted by them to achieve rapid development. This paper focused on the latest development of nano-sorbents based on ILs and DESs. The problems and bottlenecks encountered were analyzed in order to provide meaningful and valuable reference for the related research and thus promotes further development and application of green solvents-assisted nano-sorbents.